Utilization of HIV testing and counselling services by women with disabilities during antenatal care in Uganda: analysis of 2016 demographic and health survey - Hussaini Zandam (BMC, 2021)
Abstract Background HIV testing and counselling during antenatal care (ANC) is critical for eliminating mother-to-child transmission of HIV. We investigated disparity in utilization of HIV testing and counselling services (HTC) between women with and without disabilities in Uganda. Methods We conducted a retrospective study using the nationally representative 2016 Uganda Demographic and Health Survey. The study sampled 10,073 women between age 15–49 who had a live birth in the last 5 years. We estimated unadjusted and adjusted odds ratio for receiving pre-test HIV counselling, obtaining an HIV test result, and post-test HIV counselling by disability status using logistic regressions. Results We found that women with disabilities were less likely to receive pre-test HIV counselling (59.6 vs 52.4), obtain an HIV test result (68.2 vs 61.4), receive post-test HIV counselling (55.5 vs 51.6), and all HTC services (49.2 vs 43.5). From the regression analysis, women with disabilities were less likely to receive pre-test counselling [AOR = 0.83; CI = 0.74, 0.93] and obtain an HIV test result [AOR = 0.88; CI = 0.78, 0.99]. Conclusions Our findings revealed that women with disabilities are less likely to receive HTC service during ANC and highlighted the need for disability-inclusive HIV and reproductive health services. Government, non-governmental organizations, and other stakeholders should consider funding inclusive campaigns and identifying other mechanisms for disseminating health information and behavioral interventions to women with disabilities.